Unraveling drug transport mechanisms of prednisolone-loaded solid lipid nanoparticles infused with superparamagnetic iron oxide for improved transdermal drug delivery system / Nor Khaizan Anuar - Anuar, Nor Khaizan (Faculty of Pharmacy, 2024)
The primary goal of any prescribed treatment plan is to achieve specific and desirable patient outcomes, and patient adherence is crucial to this endeavour. Even the most meticulous and scientifically grounded treatment plan will not result in its therapeutic benefits if patients do not adhere to the prescribed medication regimen. Adherence to steroid treatments can be difficult, particularly for patients with chronic illnesses due to factors such as frequent dosages, the prolonged duration of treatment, and potential side effects [1]. Consequently, nonadherence to steroid medication has become increasingly prevalent among these patients, leading to significant consequences, including medication waste, disease progression, mortality, and rising healthcare costs.